Evaluation of some Biochemical and Hematological Parameters in Patients with Chronic Kidney Disease - Hadeel T. AlAni; Makarim Q. Al-Lami (مجلة كلية الطب, 2024)
Background: Chronic kidney disease is a condition that results from an indefinite change in the structure and function of the kidneys. A slow, steady progression characterizes it and is irreversible.